Characterizing Behavior, Sex and Subtype in Childhood ADHD via the Related Spectrum of Functional Network Connectivity at Rest - Emily Lundstrum; Haylee Hudson; Parth Patel; Caitlyn Busch; Channelle Gordon; Anastasia Kerr-German (BioMed)
Background/Objectives: This study investigates sex differences in the neural profiles of children with and without ADHD using functional near-infrared spectroscopy (fNIRS). Specifically, it explores the functional connectivity patterns in female and male children, considering both group membership and symptom severity scores. Methods: Participants aged 6–8 (N = 52) years performed a Passive Viewing Paradigm resting-state task while fNIRS was used to measure resting-state functional connectivity. ADHD diagnoses and subtypes were determined using the K-SADS interview, from which a continuous symptom severity score was calculated across both group and subtype. Results: The results revealed that female children with combined-type ADHD exhibited distinct neural profiles compared to male children, both overall and according to symptom severity. Male children with ADHD, across all subtypes, demonstrated less refined functional connectivity, with male children in the combined-type group showing particularly weak connectivity. Additionally, connectivity patterns varied with symptom severity: in male children, connectivity increased as symptom severity increased, while in female children, the opposite trend was observed, with connectivity decreasing as symptom severity rose. These patterns contrasted with those observed in typically developing peers. Conclusions: This study highlights significant sex differences in neural connectivity profiles in children with ADHD. Male children tend to show less refined connectivity, particularly in the combined-type subtype, whereas female children exhibit an inverse relationship between connectivity and symptom severity. These findings provide important insights into the neural mechanisms underlying ADHD and suggest that sex may play a crucial role in the neural presentation of the disorder.